2019
DOI: 10.1021/acs.jproteome.9b00004
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Atlas of the Human Brain in Alzheimer’s Disease

Abstract: The brain represents one of the most divergent and critical organs in the human body. Yet, it can be afflicted by a variety of neurodegenerative diseases specifically linked to aging, about which we lack a full biomolecular understanding of onset and progression, such as Alzheimer's Disease (AD). Here we provide a proteomic resource comprising nine anatomically distinct sections from three aged individuals, across a spectrum of disease progression, categorized by quantity of neurofibrillary tangles. Using stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 95 publications
(149 reference statements)
7
49
0
Order By: Relevance
“…To overcome this issue, we removed all proteins significantly associated with age from the list of differentially expressed proteins. Investigating the set of age-associated proteins we found that our findings were consistent with a previous report (McKetney et al, 2019), as a little overlap was presented between regions, and a large proportion of these age-related proteins was associated with extracellular exosome (p-value = 6.2e-86) and membrane (p-value = 8.9e-29).…”
Section: Relationships Of Ad-related Differentially Expressed Proteinsupporting
confidence: 91%
See 1 more Smart Citation
“…To overcome this issue, we removed all proteins significantly associated with age from the list of differentially expressed proteins. Investigating the set of age-associated proteins we found that our findings were consistent with a previous report (McKetney et al, 2019), as a little overlap was presented between regions, and a large proportion of these age-related proteins was associated with extracellular exosome (p-value = 6.2e-86) and membrane (p-value = 8.9e-29).…”
Section: Relationships Of Ad-related Differentially Expressed Proteinsupporting
confidence: 91%
“…Other authors focused on the temporal advancement of AD by investigating changes that occur in one brain area at different disease stages (Bossers et al, 2010;Hondius et al, 2016;Kim et al, 2018;Lachén-Montes et al, 2017;Lau et al, 2013;Sultana et al, 2010;Triplett et al, 2016;Zelaya et al, 2015). Both strategies were also merged through transcriptomic/proteomic investigation of brain areas considering distinct disease stages (Matarin et al, 2015;McKetney et al, 2019;Miyashita et al, 2014;Savas et al, 2017;Seyfried et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, exactly how these 12 proteins are mechanistically involved in AD remains unclear. Notably 4 of the 12 proteins are among the 1651 proteins previously differentially expressed in various regions of the brain by MS; Serine-threonine kinase receptor-associated protein, Complement factor H-related protein 1, Tropomyosin alpha-4 chain and Complement component C8 alpha chain 48 . Asparagine-tRNA ligase, cytoplasmic and Corticosteroid-binding globulin were not detected in AD and the remaining 6 were unchanged from controls 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a requirement for systematic analysis of neuronal proteome from different regions of brain. A study by McKetney et al has tried to address this by developing a proteomic atlas of nine anatomical regions of brain from three aged individuals [ 19 ]. Such atlases are helpful for understanding region specific neurodegeneration of brain.…”
Section: Proteomics Studies In Ad Pathogenesis and Biomarker Discomentioning
confidence: 99%